Loss of flavin adenine dinucleotide (FAD) impairs sperm function and male reproductive advantage in C. elegans - Chia-An Yen; Dana L Ruter; Christian D Turner; Shanshan Pang; Sean P Curran (eLife, 2020)
Exposure to environmental stress is clinically established to influence male reproductive health, but the impact of normal cellular metabolism on sperm quality is less well-defined. Here we show that impaired mitochondrial proline catabolism, reduces energy-storing flavin adenine dinucleotide (FAD) levels, alters mitochondrial dynamics toward fusion, and leads to age-related loss of sperm quality (size and activity), which diminishes competitive fitness of the animal. Loss of the 1-pyrroline-5-carboxylate dehydrogenase enzyme alh-6 that catalyzes the second step in mitochondrial proline catabolism leads to premature male reproductive senescence. Reducing the expression of the proline catabolism enzyme alh-6 or FAD biosynthesis pathway genes in the germline is sufficient to recapitulate the sperm-related phenotypes observed in alh-6 loss-of-function mutants. These sperm-specific defects are suppressed by feeding diets that restore FAD levels. Our results define a cell autonomous role for mitochondrial proline catabolism and FAD homeostasis on sperm function and specify strategies to pharmacologically reverse these defects.